2019
DOI: 10.1111/jcmm.14499
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the promoter of TUG1 is associated with an increased risk of ischaemic stroke

Abstract: Taurine‐upregulated gene 1 (TUG1), a kind of long non‐coding RNAs (lncRNAs), was up‐regulated in ischaemic stroke (IS) with the function of promoting neuron apoptosis. In this study, we aimed to investigate the association of TUG1 polymorphisms with IS risk. The TUG1 polymorphisms were genotyped using a custom‐by‐design 48‐Plex SNPscan kit. The promoter activity was measured using the dual luciferase reporter assay. Relative expression of TUG1 in IS patients was analysed using quantitative PCR and the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Actually, increasing studies focused on SNPs of lncRNA involved in process of IS. For example, the rs2240183 C allele of lncRNA TUG1 was associated with a higher risk of IS by possibly binding to GATA-1 and elevating TUG1 levels [19]. The lncRNA ANRIL rs2383207 increased the risk of IS by 1.52-fold under the recessive model [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, increasing studies focused on SNPs of lncRNA involved in process of IS. For example, the rs2240183 C allele of lncRNA TUG1 was associated with a higher risk of IS by possibly binding to GATA-1 and elevating TUG1 levels [19]. The lncRNA ANRIL rs2383207 increased the risk of IS by 1.52-fold under the recessive model [20].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, SNPs of lncRNAs have been verified to be associated with IS susceptibility, such as the rs217727 C > T and rs4929984 C > A in lncRNA H19 and the rs2240183 in promoter of lncRNA TUG1 [19][20][21]. It was reported that genetic variants in the promoter region could affect the expression, subcellular localization and structure stability, ultimately affecting progression of relevant diseases [22].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, increasing association studies focused on SNPs of lncRNA involved in process of IS. For example, the rs2240183 C allele of lncRNA TUG1 was associated with a higher risk of IS possibly by binding to GATA-1 and elevating TUG1 levels [20], the ANRIL rs2383207 increased the risk of IS by 1.52-fold under the recessive mode [21], the rs217727 TT and rs4929984 AA in the H19 increase the risk of IS, with adjusted OR 4.288, 3.020 respectively [22]. Those provide a new perspective on the genetic mechanism of IS.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, single nucleotide polymorphism (SNP) of lncRNAs have been proved to be associated with IS susceptibility, such as the rs217727 C>T and rs4929984 C>A in lncRNA H19, the rs2240183 C allele in promoter of lncRNA TUG1 [20][21][22]. It was reported that genetic variants in the promoter region can affect disease occurrence by involving in transcription efficiency, genetic stability and function [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, single nucleotide polymorphism (SNP) of lncRNAs have been proved to be associated with IS susceptibility, such as the rs217727 C > T and rs4929984 C > A in lncRNA H19, the rs2240183 C allele in promoter of lncRNA TUG1 [18][19][20]. It was reported that genetic variants in the promoter region can affect the expression, subcellular localization, structure stability, and ultimately involve in function and disease progression [21].…”
mentioning
confidence: 99%